THE INFLUENCE OF SOCIAL MEDIA IN CHOOSING PROVISIONS BASED ON IDEOLOGICAL THINKING MILENIAL’S GENERATION IN SERANG CITY (CASE STUDY PRESIDENTIAL ELECTION 2019) - Iman Mukhroman; Rangga Galura Gumelar (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2020)
The biggest democracy event in Indonesia has been carried out, where there must be a democratic party mandating general elections between the presidential and parliamentary elections at the Central, Provincial and Regency / City levels as well as the regional councils which at present, still leaves problems actually. Many victims on the grass root who escort the election who became victims of the conflict, in addition to that on social media related to the recapitulation results as if still giving many questions to the election organizers to then provide transparency data. The elections this year did provide a surprise-direction and direction of movement in the democratic system that we are building today. The Milenial’s generation who had a very large voting presentation in the special vote in the 2019 presidential election, has big influences for both candidates, Joko Widodo - KH. Ma’ruf Amin, and  Prabowo Subianto - Sandiaga Uno. Flow of  information on new platform of media, in this case social media created as a political communication strategy tool in campaigning the two candidates to milenials. Based on research using a positivistic perspective on quantitative estimates that process data based on the number of samples that have been determined in the existing population. Analysis of the data from the results of the questionnaire disseminated to the sample is, then analyzed using path analysis or path analysis, so that it will show how the actual between the top-level variables and their effects. The results of this study also answer the linkage of the Serang City milineal as a measurement and barometer that can be accounted for either theoretically or methodologically. Keywords: Millennials, 2019 Presidential Election, Serang City